2021
DOI: 10.1111/ijcp.14563
|View full text |Cite
|
Sign up to set email alerts
|

An emergency plan for management of COVID‐19 patients in rural areas

Abstract: Aims of the study To describe the experience of six hospitals in the management of COVID‐19 patients in rural areas through an assessment of proportions, types and clinical outcomes of remote clinical interventions. Methods This was a prospective observational study conducted in six Egyptian hospitals over a period five months. An emergency response was implemented in each hospital in order to connect clinical pharmacists with COVID‐19 patients living in rural areas. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…After removing duplicates (n=795), and screening by the title and abstract (n=230) and full text (n=121), 43 articles were included in this review 20–62. Among the included studies were 25 observational studies (including 13 cross-sectional studies,36–39 43–48 54 59 60 5 case series,34 35 49–51 5 retrospective study,40 41 52 53 55 1 prospective study61 and 1 interview study42 and 18 descriptive studies 20–33 56–58 62. The general characteristics of the included studies are summarised in online supplemental table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates (n=795), and screening by the title and abstract (n=230) and full text (n=121), 43 articles were included in this review 20–62. Among the included studies were 25 observational studies (including 13 cross-sectional studies,36–39 43–48 54 59 60 5 case series,34 35 49–51 5 retrospective study,40 41 52 53 55 1 prospective study61 and 1 interview study42 and 18 descriptive studies 20–33 56–58 62. The general characteristics of the included studies are summarised in online supplemental table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the included studies are summarised in online supplemental table 1. The majority of the studies reported about the use of eHealth by hospital pharmacists,20 21 23 25 29–31 33–35 37–41 43 46–49 52–55 58 59 61 followed by community pharmacists 28 35 45 46 50 51 54 60 62. Patients with chronic diseases27 31 32 34 37 39 40 43 44 48 52 54 57 60–62 were the primary targets populations of PC-eHealth interventions, followed by patients with COVID-1926 34 42 46 49–51 58 and patients with cancer 27 31 37 40…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementing hospital telepharmaceutical services reduces irrational medicines and improves clinical outcomes for COVID-19 patients in rural areas. 38 Vietnam develops for their rural areas a ‗Rapid Action Team' with the participation of all community stakeholders, including health workers (public and private health staff, retired health professionals), police, soldiers, teachers, community organizations, and communities. This grassroots health system mobilizes and prioritizes all its financial resources from the State budget and contributions from donors and non-governmental organizations to supply medical equipment and supplies.…”
mentioning
confidence: 99%